EXPORTS-R&D INVESTMENT COMPLEMENTARITY AND ECONOMIC PERFORMANCE OF FIRMS LOCATED IN PORTUGAL - Neves, Alexandre; Teixeira, Aurora A. C.; Silva, Sandra T. (Investigación Económica, 2016)
There are a vast number of studies on the relationship between R&D and exports. However, the results are not always clear-cut. This study evaluates whether, in the case of a small, open and peripheral country in which exports are the engine of economic growth despite a noticeable laggardness in terms of R&D, the firms’ R&D impacts on and/or is influenced by their exports, as well as whether the interrelation between R&D and exports impacts on the performance of firms. Using an unique dataset comprising all (more than 340 thousands) non-financial companies based in Portugal, over the period 2006-2012, estimations based on bivariate probit models, which provide the simultaneous estimation of the two decisions (R&D and exports), taking into account the correlation between the estimation errors of the equations for R&D and exports, confirm there is complementarity between R&D and exports, which means that engaging in R&D activities will increase the firm’s probability of engaging in export activities. Additionally, engaging in export activities will also increase the probability of engaging in R&D. The results also provide support for the hypothesis that more productive firms self-select into exporting activities and also provide support for the learning-by-exporting hypothesis. Finally, based on a panel model we further found that R&D and exports have a positive effect on sales growth, which is enhanced when both activities occur simultaneously.